Current practices are variable in the evaluation and management of patients with anomalous aortic origin of a coronary artery: Results of a survey. (2nd July 2017) - Agrawal, Hitesh; Mery, Carlos M.; Day, Patrick E.; Sexson Tejtel, S. Kristen; McKenzie, E. Dean; Fraser, Charles D.; Qureshi, Athar M.; Molossi, Silvana
Abstract: Background: Anomalous aortic origin of a coronary artery (AAOCA) is the second leading cause of sudden cardiac death in young athletes in the USA. Long‐term outcome data for these patients are lacking to date. There is insufficient knowledge on the best approach to these patients and they are managed in a nonuniform manner. Methods: An online survey of 15 questions regarding management of AAOCA was sent out to 198 cardiac healthcare providers. The goal was to define gaps in knowledge to justify a dedicated scientific forum for discussion of AAOCA. Descriptive statistics were performed. Results: A total of 91 providers (46%) completed the survey including pediatric cardiology subspecialists (40%), general pediatric cardiologists (24%), cardiovascular (CV) surgeons (22%), adult cardiologists (10%), nurse practitioners (8%), cardiology fellows (3%) and CV anesthesiologist (1%). Forty‐eight percent had been practicing for over 15 years and 28% were in their first 5 years of practice. Fifty‐two percent of the providers cared for adults and 93% cared for children/adolescents. Eighty‐eight percent were affiliated with an academic institution. All but one provider practiced in the USA, 62% practiced in Texas. Half of participants (50%) were very comfortable managing AAOCA patients and 36% were somewhat comfortable. Providers utilized various imaging tests to confirm the anatomy including computed tomography angiography 88%, cardiac magnetic resonance imaging 70%, cardiac catheterization 60%, echocardiogram 12%, IVUS 2% and myocardial perfusion scan 1%. The majority felt comfortable in counseling the families and felt that depending on the type of lesion these patients should get surgical referral (85%) vs clinical follow up (67%) with exercise restriction (65%). Conclusion: There is heterogeneity in the way AAOCA patients are currently evaluated and managed. A knowledge gap exists even with participants from academic institutions. Long‐term data with a defined approach to management of these patients may help to improve outcomes and prevent unnecessary exercise restriction or surgery.